DINAMIKA IMPLEMENTASI AKAD JUAL BELI PROPERTI SYARIAH NON BANK - Bintang, Ikhsan; Suman, Agus (Islamic Economics and finance in Focus, 2023)
This research aims to see the dynamics that occur in the sharia contract scheme used in the Rumahku Surgaku program, starting from the validity of the contract used, the advantages of the program used, then the problems that occur in the contract process as well as the precautions and solutions made to overcome these problems. This research uses primary data from interviews with informants involved, and secondary data obtained from dissertations, literature, articles, journals, and internet sites. The research is qualitative and descriptive. The results of this study indicate that the contract used in the Rumahku Surgaku program is legally valid through the DSN MUI fatwa. The dynamics that occur include consumer literacy issues, sharia marketing needs, risk analysis needs, defaults, payment delays, sale and purchase cancellations, and fines that overlap with applicable law. As an action, a draft contract is made, educating consumers, conducting studies and training for employees, and implementing deliberation, and as a solution, sanctions are imposed for breach of promise, applying compensation for cancellation of sale and purchase, giving consumers the right to complain about product discrepancies, establishing Islamic estate management, and the right to seek assistance from legal institutions if there are problems that cannot be resolved by deliberation.